2020
DOI: 10.1161/jaha.120.017580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus Disease 2019 (COVID‐19) on Patients With Congenital Heart Disease Across the Lifespan: The Experience of an Academic Congenital Heart Disease Center in New York City

Abstract: Background We sought to assess the impact and predictors of Coronavirus Disease 2019 (COVID‐19) infection and severity in a cohort of congenital heart disease (CHD) patients at a large CHD center in New York City. Methods and Results We performed a retrospective review of all individuals with CHD followed at Columbia University Irving Medical Center who were diagnosed with COVID‐19 between 3/1/2020 and 7/1/2020. The primary endpoint was moderate/severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
78
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 22 publications
5
78
1
1
Order By: Relevance
“…In specific response to their cited article by Lewis et al, the results of which they claim to be contrary to our findings, we proffer that a single study cannot be used to generalize outcomes over a large population of CHD patients [7]. Furthermore, their finding of lacking the correlation between the complexity of CHD and the severity of infection-related cardiac decompensation does not disqualify CHD from being a predictor of worse prognosis in itself.…”
contrasting
confidence: 99%
“…In specific response to their cited article by Lewis et al, the results of which they claim to be contrary to our findings, we proffer that a single study cannot be used to generalize outcomes over a large population of CHD patients [7]. Furthermore, their finding of lacking the correlation between the complexity of CHD and the severity of infection-related cardiac decompensation does not disqualify CHD from being a predictor of worse prognosis in itself.…”
contrasting
confidence: 99%
“…Our data are in line with the positive outcome described in 10 Fontan patients in a single-centre US study 6 . These results may be partially explained with the observation that, despite the above-described multiple implications of Covid-19, patients with single-ventricle might be protected by younger age, patients’ education to self-isolation and chronic treatment with anticoagulants/antiplatelets, which were showed to improve the outcome 7 , 8 Interestingly, according to the 2018 ACC/AHA ACHD guidelines 9 , 6 out of 7 patients in our study had an advanced physiological stage, which was reported as a risk factor of adverse outcome in ACHD patients5. Patients with failing Fontan or unstable haemodynamics may be at higher risk of complications from Covid-19.…”
supporting
confidence: 91%
“…As such, they have largely been considered high risk and often adopt a highly restrictive lifestyle and employment choices accordingly. Early publications in CHD reported different risks ( 7 , 8 ) but suggested worse risk in higher physiological stages ( 9 ).…”
mentioning
confidence: 99%